2023
DOI: 10.3390/microorganisms11071765
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Strategies to Control Salmonella Infantis: An Emerging Challenge in the European Broiler Sector

Abstract: Salmonella spp. has been globally recognized as one of the leading causes of acute human bacterial gastroenteritis resulting from the consumption of animal-derived products. Salmonella Enteritidis, S. Typhimurium, and its monophasic variant are the main serovars responsible for human disease. However, a serovar known as S. Infantis has emerged as the fourth most prevalent serovar associated with human disease. A total of 95% of isolated S. Infantis serovars originate from broilers and their derived products. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 125 publications
0
16
0
Order By: Relevance
“…Since 2014, S. Infantis has by far been the no. 1 serovar isolated in broiler production in many MSs (Montoro-Dasi et al, 2023); such phenomena could also occur with other serovars, which are progressively increasing in other poultry populations. For instance, over the last couple of years, S. Anatum and S. Agona were reported in turkeys and ranked in the top positions for the serovars identified, even though their notification from human cases is rather uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2014, S. Infantis has by far been the no. 1 serovar isolated in broiler production in many MSs (Montoro-Dasi et al, 2023); such phenomena could also occur with other serovars, which are progressively increasing in other poultry populations. For instance, over the last couple of years, S. Anatum and S. Agona were reported in turkeys and ranked in the top positions for the serovars identified, even though their notification from human cases is rather uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Infantis has by far been the no. 1 serovar isolated in broiler production in many MSs (Montoro‐Dasi et al., 2023 ); such phenomena could also occur with other serovars, which are progressively increasing in other poultry populations. For instance, over the last couple of years, S .…”
Section: Discussionmentioning
confidence: 99%
“…However, bacterial contamination on broiler farms is increasingly related to the S . Infantis serotype [ 21 , 22 , 23 ]. Other relevant serotypes associated with chicken meat in Germany and Vietnam are S .…”
Section: Introductionmentioning
confidence: 99%
“…Although different serotypes have been associated with salmonellosis, recent studies have reported Salmonella enterica subsp. enterica serovar Infantis as being widely spread through chicken meat [1,11] and Salmonella enterica subsp. enterica serovar Enteritidis through eggs [1,12].…”
Section: Introductionmentioning
confidence: 99%